2017
DOI: 10.18632/oncotarget.20726
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of BAG3 inhibits the epithelial-mesenchymal transition in human cervical cancer

Abstract: Bcl2-associated athanogene 3 (BAG3) has been reported to be involved in aggressive progression of many tumors. In the present study, we examined the expression of BAG3 in human cervical cancer (CC) tissues and investigated the role of BAG3 in SiHa and HeLa cell growth, migration, and invasion. Here, we found that most of CC tissues highly expressed the protein and mRNA of BAG3, while their expression was obviously lower in paired normal tissues (all p<0.001). BAG3 expression was associated with FIGO stage and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…Previous reports also suggested that miR-206 can regulate different target genes to function in diverse cell processes, such as cell differentiation, proliferation, and apoptosis 14–16 . In addition, B-cell lymphoma 2 (Bcl-2)-associated athanogene 3 (BAG3) is also involved in multiple biological processes of CC, including cell proliferation, migration, and invasion 17 . However, the expression and role of the miR-206/BAG3 pathway in human CC are still elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports also suggested that miR-206 can regulate different target genes to function in diverse cell processes, such as cell differentiation, proliferation, and apoptosis 14–16 . In addition, B-cell lymphoma 2 (Bcl-2)-associated athanogene 3 (BAG3) is also involved in multiple biological processes of CC, including cell proliferation, migration, and invasion 17 . However, the expression and role of the miR-206/BAG3 pathway in human CC are still elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Several reports have suggested EMT regulation as a mechanism that promotes the development of aggressive phenotype by BIS (11,29,30). However, most previous reports only reported changes in the EMT phenomena as a result of quantitative changes in BIS, and specific details on how BIS can affect EMT have not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, siRNA-mediated depletion of BAG3 inhibits epithelial-mesenchymal transition (EMT) in cervical cancer cell lines in vitro and reduced tumor sizes in xenograft mouse model in vivo. This was accompanied by reduction of the EMT-regulator Slug and N-Cadherin and MMP2 as marker protein for the mesenchymal state and an increase in E-Cadherin, indicating an epithelial state [58].…”
Section: Cervical Cancermentioning
confidence: 97%
“…In cervical cancer, BAG3 expression was shown to correlate with tumor grade [57,58]. Additionally, siRNA-mediated depletion of BAG3 inhibits epithelial-mesenchymal transition (EMT) in cervical cancer cell lines in vitro and reduced tumor sizes in xenograft mouse model in vivo.…”
Section: Cervical Cancermentioning
confidence: 99%